PENGARUHÃÂ KELENGKAPANÃÂ PERALATANÃÂ PRAKTIKÃÂ DANÃÂ PENERAPANÃÂ KESELAMATANÃÂ ÃÂ DANÃÂ KESEHATANÃÂ KERJAÃÂ TERHADAPÃÂ HASILÃÂ BELAJARÃÂ KOMPETENSIÃÂ PERBAIKANÃÂ KOPLINGÃÂ ÃÂ ÃÂ - Ami, Ridwan; Masugino, -; PramonoÃƒÂ‚Ã‚Â , - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
PenelitianÃÂ iniÃÂ bertujuanÃÂ untukÃÂ mengetahuiÃÂ seberapaÃÂ besarÃÂ pengaruhÃÂ kelengkapanÃÂ peralatanÃÂ praktikÃÂ danÃÂ penerapanÃÂ keselamatanÃÂ danÃÂ kesehatanÃÂ kerjaÃÂ terhadapÃÂ hasilÃÂ belajarÃÂ kompetensiÃÂ perbaikanÃÂ koplingÃÂ diÃÂ SMKÃÂ NÃÂ 1ÃÂ AdiwernaÃÂ KabupatenÃÂ TegalÃÂ menurutÃÂ persepsiÃÂ siswa.ÃÂ SampelÃÂ dalamÃÂ penelitianÃÂ iniÃÂ sebanyakÃÂ 70ÃÂ siswaÃÂ yangÃÂ diambilÃÂ menggunakanÃÂ teknikÃÂ totalÃÂ sampling.ÃÂ MetodeÃÂ pengambilanÃÂ dataÃÂ menggunakanÃÂ angketÃÂ yangÃÂ telahÃÂ diujiÃÂ validitasÃÂ reliabilitasnya.ÃÂ MetodeÃÂ analisisÃÂ dataÃÂ danÃÂ hipotesisÃÂ menggunakanÃÂ analisisÃÂ regresiÃÂ duaÃÂ prediktor.ÃÂ HasilÃÂ penelitianÃÂ menunjukkanÃÂ bahwaÃÂ kelengkapanÃÂ peralatanÃÂ praktikÃÂ danÃÂ penerapanÃÂ keselamatanÃÂ danÃÂ kesehatanÃÂ kerjaÃÂ secaraÃÂ bersamaÃ¢â¬ÂsamaÃÂ memberikanÃÂ pengaruhÃÂ terhadapÃÂ hasilÃÂ belajarÃÂ kompetensiÃÂ perbaikanÃÂ koplingÃÂ diÃÂ SMKNÃÂ 1ÃÂ AdiwernaÃÂ KabupatenÃÂ Tegal.ÃÂ DisarankanÃÂ kepadaÃÂ sekolahÃÂ untukÃÂ meningkatkanÃÂ kelengkapanÃÂ peralatanÃÂ praktiknyaÃÂ danÃÂ guruÃÂ untukÃÂ selaluÃÂ mengawasiÃÂ siswaÃÂ padaÃÂ saatÃÂ pembelajaranÃÂ praktikÃÂ berlangsungÃÂ agarÃÂ siswaÃÂ terkontrolÃÂ jikaÃÂ adaÃÂ siswaÃÂ yangÃÂ tidakÃÂ menerapkanÃÂ keselamatanÃÂ danÃÂ kesehatanÃÂ kerja. ÃÂ KataÃÂ kunci:ÃÂ KelengkapanÃÂ peralatanÃÂ praktik,ÃÂ keselamatanÃÂ danÃÂ kesehatanÃÂ kerja,ÃÂ hasilÃÂ belajarÃÂ ÃÂ TheÃÂ aimÃÂ ofÃÂ theÃÂ researchÃÂ isÃÂ toÃÂ discoverÃÂ howÃÂ muchÃÂ theÃÂ effectÃÂ ofÃÂ practiceÃÂ toolÃÂ completeness,ÃÂ workingÃÂ healthÃÂ andÃÂ safetyÃÂ applicationÃÂ towardÃÂ competenceÃÂ studyÃÂ resultÃÂ ofÃÂ clutchÃÂ repairÃÂ isÃÂ atÃÂ SMKÃÂ NÃÂ 1ÃÂ AdiwernaÃÂ inÃÂ TegalÃÂ RegencyÃÂ acÃ¢â¬ÂcordingÃÂ toÃÂ studentsÃ¢â¬â¢ÃÂ perceptions.ÃÂ TheÃÂ sampleÃÂ ofÃÂ theÃÂ researchÃÂ wasÃÂ aboutÃÂ 70ÃÂ studentsÃÂ chosenÃÂ usingÃÂ totalÃÂ samplingÃÂ technique.ÃÂ DataÃÂ wasÃÂ gotÃÂ usingÃÂ questionnaireÃÂ havingÃÂ beenÃÂ testedÃÂ inÃÂ validityÃÂ ofÃÂ itsÃÂ reliability.ÃÂ Meanwhile,ÃÂ theÃÂ dataÃÂ andÃÂ hypothesisÃÂ wereÃÂ analyzedÃÂ usingÃÂ twoÃ¢â¬ÂpredictorÃÂ regressionÃÂ analysis.ÃÂ TheÃÂ resultÃÂ ofÃÂ theÃÂ researchÃÂ indicatesÃÂ thatÃÂ practiceÃÂ toolÃÂ completeness,ÃÂ workingÃÂ healthÃÂ andÃÂ safetyÃÂ applicationÃÂ simultaneouslyÃÂ contributeÃÂ impactÃÂ towardÃÂ competenceÃÂ studyÃÂ resultÃÂ ofÃÂ clutchÃÂ repairÃÂ atÃÂ SMKÃÂ NÃÂ 1ÃÂ AdiwernaÃÂ inÃÂ TegalÃÂ Regency.ÃÂ ItÃÂ isÃÂ suggestedÃÂ toÃÂ hadmasterÃÂ toÃÂ affordÃÂ theÃÂ practiceÃÂ toolÃÂ completenessÃÂ andÃÂ toÃÂ teachersÃÂ toÃÂ keepÃÂ theirÃÂ eyesÃÂ onÃÂ studentsÃÂ whenÃÂ aÃÂ learningÃÂ practiceÃÂ lastsÃÂ soÃÂ thatÃÂ theÃÂ studentsÃÂ areÃÂ inÃÂ controlÃÂ andÃÂ alwaysÃÂ concernÃÂ withÃÂ workingÃÂ healthÃÂ andÃÂ safety. ÃÂ Keywords:ÃÂ practiceÃÂ toolÃÂ completeness,ÃÂ workingÃÂ healthÃÂ andÃÂ safety,ÃÂ studyÃÂ result